Bacterial RNA: an underestimated stimulus for innate immune responses - Eigenbrod, Tatjana; Dalpke, Alexander (The journal of immunology, 2015)
Although DNA of bacterial and viral origin, as well as viral RNA, have been intensively studied as triggers of innate immune responses, the stimulatory properties of bacterial RNA and its role during infections have just begun to be deciphered. Bacterial RNA is a strong inducer of type I IFN and NF-κB-dependent cytokines, and it also can activate the Nlrp3 inflammasome. In this review, we focus on the receptors and signaling pathways involved in innate immune activation by bacterial RNA and analyze the physiological relevance of bacterial RNA recognition during infections. Furthermore, we present the concept that RNA modifications can impair RNA-dependent immune activation. RNA modifications differ between eukaryotes and prokaryotes; thus, they can serve to define the innate pattern that is recognized. In this regard, we discuss the role of ribose 2′-O-methylation as a potential immune-escape mechanism.